Are natural resource windfalls a blessing or a curse in democratic settings: a case study - Ghana? - Siakwah, Pius (Trinity College (Dublin, Ireland). Department of Geography, 2016)
SUMMARY OF METHODS AND FINDINGS: In order to analyse the problematic impact of oil on Ghana's development, this study relied on qualitative methods, supported by descriptive statistics, tables and graphs. These qualitative and quantitative methods complement each other to explain the problematic impact of oil. Qualitative methods used for data collection include semi-structured interviews, focus groups and document reviews. A survey was conducted with fisher-folks to assess the impact of the oil exploration on local livelihoods, income, poverty and the relationship with oil companies and the government. Triangulation of diverse methodologies helped to present the diversity of views, increased the credibility and trustworthiness of the data and research findings. Twenty-five key informant interviews were conduct to understand the impact of the oil industry on Ghana. The key informants included politicians and policy makers in Ghana, CSOs, executives from Kosmos and Tullow. Institutions and CSOs that informant interviewees were chosen from included; Ghana National Petroleum Corporation, Ministry of Petroleum, Ministries of Finance and Economic Planning, Ministry of Agriculture, Ghana Energy Commission and Environmental Protection Agency. Others included the Ghana Statistical Service, Bank of Ghana, Institute of Social, Statistical and Economic Research, Commission on Human Right and Administrative Justice, Integrated Social Development Centre, Centre for Democratic Development, and Africa Centre for Energy Policy. Themes discussed with the informants differ based on the knowledge of oil industry and how the activities of institution are related to it. Issues discussed included; the impact of oil on employment, agriculture and industrial development, governance, institutions and corruption and conflicts. Other issues focused on the impact of oil on economic growth, currency movement and environmental challenges such as gas flaring, pollution, waste management, and loss of biodiversity. Eighty semi-structured interviews were conducted in Dixcove with fishermen, fishmongers and other community members to explore the impact of oil on local incomes, employment, economic activities, poverty and inequality, provision of social services, oil-related conflicts, and environmental pollution. Three focus groups were also organised to discuss how fishing restrictions impacted local incomes, livelihoods and employment. A survey was used to collect data from Dixcove to assess the impact of the oil exploration on local livelihoods, income, poverty and their relationship with oil companies. Data for this research was analysed by identifying common and divergent ideas, developing themes and relating them to existing ones. Descriptive statistics such as tables and graphs were used to illustrate changes in incomes, currency movement, GDP, agricultural and industrial and impact of oil on local employment. This study revealed that oil is problematic for development in developing countries, even in a democratic setting due to the negative impacts of oil; global, national and local politics and interests. The impact of oil on Ghana showed that although resources windfalls are problematic for development, the challenges are socially produced, shaped and conditioned by a country's political economy and its interaction with the negative impacts of oil, global politics, structures and actors, which formed a 'globalised assemblage'. How oil windfalls are utilised is shaped and conditioned through interactions between heterogeneous actors, agencies and structures. Due colonial legacy, the economy of Ghana is characterised by a lop-sided dependence on the export of raw materials, and the import of manufactured goods. Ghana's economy is integrated into the global economy in ways that makes unfavourable and ensures structural dependency. Oil has only help Ghana to diversify its dependency on gold, timber and cocoa. There have not been structural changes in the national economy, it is instead reinforcing and reconstruction of the country's deep seated structural dependency. Ghana's case also revealed that although democracy does not insulate a country from the problematic impacts of oil, it can mitigate them. The Ghana case also revealed that the directionality of the problematic elements associated with oil-based development is not predetermined. For instance, while the resource curse literature noted that resource windfalls often leads to local currency appreciation, the Ghana cedi has defied this. Oil export has not reversed the depreciation of the local currency, indicating that the impact resources windfalls on currency movement are embedded in the globalised socio-economic and political conditions. This study also revealed that there are temporalities and spatialities to the problematic nature of oil and development in the developing world. Temporally, increased Ghana government borrowing, backed by oil is creating a 'deferred or delayed debt curse' where future generation will be burdened with, and spatially, whereas oil has had positive impacts on the provision of social services and generated some employment, the fisher-folks experienced decline in income due to restrictions on fishing in the sea near their locality. The study revealed that whereas the incidence of poverty in Dixcove is not as bad as compared to other parts of the country, it is unevenly distributed among the people, with fishermen and fishmongers in the area experiencing decline in income. The impact of oil on development is differentiated across sectors and spaces, and manifest unevenly. This study argues that while democracy does not insulate a country from the problematic impacts of oil, it mitigates them. The directionality of the problematic elements associated with oil development is not predetermined, they have temporal and spatial dimensions and are embedded in the existing socio-economic and political conditions SUMMARY OF METHODS AND FINDINGS: In order to analyse the problematic impact of oil on Ghana's development, this study relied on qualitative methods, supported by descriptive statistics, tables and graphs. These qualitative and quantitative methods complement each other to explain the problematic impact of oil. Qualitative methods used for data collection include semi-structured interviews, focus groups and document reviews. A survey was conducted with fisher-folks to assess the impact of the oil exploration on local livelihoods, income, poverty and the relationship with oil companies and the government. Triangulation of diverse methodologies helped to present the diversity of views, increased the credibility and trustworthiness of the data and research findings. Twenty-five key informant interviews were conduct to understand the impact of the oil industry on Ghana. The key informants included politicians and policy makers in Ghana, CSOs, executives from Kosmos and Tullow. Institutions and CSOs that informant interviewees were chosen from included; Ghana National Petroleum Corporation, Ministry of Petroleum, Ministries of Finance and Economic Planning, Ministry of Agriculture, Ghana Energy Commission and Environmental Protection Agency. Others included the Ghana Statistical Service, Bank of Ghana, Institute of Social, Statistical and Economic Research, Commission on Human Right and Administrative Justice, Integrated Social Development Centre, Centre for Democratic Development, and Africa Centre for Energy Policy. Themes discussed with the informants differ based on the knowledge of oil industry and how the activities of institution are related to it. Issues discussed included; the impact of oil on employment, agriculture and industrial development, governance, institutions and corruption and conflicts. Other issues focused on the impact of oil on economic growth, currency movement and environmental challenges such as gas flaring, pollution, waste management, and loss of biodiversity. Eighty semi-structured interviews were conducted in Dixcove with fishermen, fishmongers and other community members to explore the impact of oil on local incomes, employment, economic activities, poverty and inequality, provision of social services, oil-related conflicts, and environmental pollution. Three focus groups were also organised to discuss how fishing restrictions impacted local incomes, livelihoods and employment. A survey was used to collect data from Dixcove to assess the impact of the oil exploration on local livelihoods, income, poverty and their relationship with oil companies. Data for this research was analysed by identifying common and divergent ideas, developing themes and relating them to existing ones. Descriptive statistics such as tables and graphs were used to illustrate changes in incomes, currency movement, GDP, agricultural and industrial and impact of oil on local employment. This study revealed that oil is problematic for development in developing countries, even in a democratic setting due to the negative impacts of oil; global, national and local politics and interests. The impact of oil on Ghana showed that although resources windfalls are problematic for development, the challenges are socially produced, shaped and conditioned by a country's political economy and its interaction with the negative impacts of oil, global politics, structures and actors, which formed a 'globalised assemblage'. How oil windfalls are utilised is shaped and conditioned through interactions between heterogeneous actors, agencies and structures. Due colonial legacy, the economy of Ghana is characterised by a lop-sided dependence on the export of raw materials, and the import of manufactured goods. Ghana's economy is integrated into the global economy in ways that makes unfavourable and ensures structural dependency. Oil has only help Ghana to diversify its dependency on gold, timber and cocoa. There have not been structural changes in the national economy, it is instead reinforcing and reconstruction of the country's deep seated structural dependency. Ghana's case also revealed that although democracy does not insulate a country from the problematic impacts of oil, it can mitigate them. The Ghana case also revealed that the directionality of the problematic elements associated with oil-based development is not predetermined. For instance, while the resource curse literature noted that resource windfalls often leads to local currency appreciation, the Ghana cedi has defied this. Oil export has not reversed the depreciation of the local currency, indicating that the impact resources windfalls on currency movement are embedded in the globalised socio-economic and political conditions. This study also revealed that there are temporalities and spatialities to the problematic nature of oil and development in the developing world. Temporally, increased Ghana government borrowing, backed by oil is creating a 'deferred or delayed debt curse' where future generation will be burdened with, and spatially, whereas oil has had positive impacts on the provision of social services and generated some employment, the fisher-folks experienced decline in income due to restrictions on fishing in the sea near their locality. The study revealed that whereas the incidence of poverty in Dixcove is not as bad as compared to other parts of the country, it is unevenly distributed among the people, with fishermen and fishmongers in the area experiencing decline in income. The impact of oil on development is differentiated across sectors and spaces, and manifest unevenly. This study argues that while democracy does not insulate a country from the problematic impacts of oil, it mitigates them. The directionality of the problematic elements associated with oil development is not predetermined, they have temporal and spatial dimensions and are embedded in the existing socio-economic and political conditions
Keywords: Geography, Ph.D.; Ph.D. Trinity College Dublin